Perioperative administration of propranolol to women undergoing ovarian cancer surgery: A pilot study - Jang, Hye-In (Obstet Gynecol Sci, 2017)
OBJECTIVE: This study was done to evaluate whether perioperative propranolol (ß-blocker) in ovarian cancer patients undergoing debulking surgery reduced perioperative tumor growth induced by surgical stress. METHODS: This was a prospective randomized single institution analysis. The primary objective was to compare the changes in CA 125 level (changes between preoperation day 2 and postoperative day 7). As a study arm, patients received a low dose of propranolol 40 mg/day (4×10 mg) starting two days before surgery and 40 mg twice daily for three days following surgery. RESULTS: Twenty-two patients were enrolled and 16 were evaluable for efficacy. The drug was well tolerated. The mean decrease of CA 125 during the seven perioperative days was 83.1±8.9% in the propranolol group and 72.4±14.7% in the placebo group. The difference was statistically significant (P=0.044). The change of C-reactive protein, cortisol, and anxiety score (State-Trait Anxiety Inventory-X1) were not different between the two groups. CONCLUSION: This preliminary result is the first to directly test the role of perioperative propranolol on tumor growth. Even with the small sample size and short term use of the drug, perioperative propranolol was effective in reducing tumor burden (as measured by CA 125) suggesting its potential benefits in decreasing perioperative tumor growth.